The trade competitiveness of palm-biodiesel in renewable energy market - Norashida Othman,; Zulkornain Yusop,; Mohd Mansor Ismail,; Syamsul Herman Mohammad Afandi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Following the decline of Malaysian biodiesel export revenue since 2009, the value has been fluctuating in recent years amid fierce global competition. Thus, it is important to assess the competitiveness of Malaysia-produced biodiesel. In comparison to other major biodiesel-producing countries including Indonesia, the United States of America, and Germany. Hence, this paper aimed to investigate the competitiveness of the Malaysian biodiesel industry based on the Relative Trade Advantage (RTA) indices with respect to the main competitors. Data from 2012 to 2016 were analyzed for selected biodiesel commodities. The RTA index indicated that Malaysia could potentially grow further despite being a minor producer. Hence, there is a need to strengthen the palm oil industry as it can be a definite source of higher export earnings.